Social Dancing as Embodied Practice: Localization and Community Functions in the Southern Philippines (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
Social dancing is an important yet understudied form of physical culture in Philippine community life. This qualitative case study examined how Western-originated social dances were adapted and sustained in communities across the Southern Philippines, focusing on their roles in physical activity, social connection, and cultural continuity. Eighteen participants, including dancers, instructors, organizers, and cultural workers, were engaged through semi-structured interviews, participant observation at twelve dance events, and document review. Thematic analysis identified four key dimensions, namely cultural adaptation through local music and movement, inclusive participation across diverse groups, institutional support from schools and local governments, and psychosocial benefits such as well-being, identity affirmation, and community bonding. The findings indicate that social dancing functions as an accessible physical recreation while also supporting cultural transmission and community cohesion. The study contributes to scholarship on physical culture in Southeast Asia and offers implications for physical education, community health, and cultural preservation.